2021
DOI: 10.3126/janr.v4i2.33679
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perception on status of livestock insurance in Surkhet district, Nepal

Abstract: Livestock is an important sector for sustained livelihoods of Nepalese people, particularly for small holder farmers. However, occurrence of any disease or disaster may get livestock as the source of sufferings.  Livestock insurance can come up as an effective tool for risk management in livestock sector.  This study covers the current status and perception of the farmers on livestock insurance. A total of 45 livestock farmers were selected purposively from three municipalities (15 from each municipality) in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
3
1
0
Order By: Relevance
“…The age distribution of producers revealed that the maximum number of people involved in Chhurpi production was in between 20–30 and 30–40 years of age. This result concurs with the findings of Paudel [ 37 ] and Nepali [ 38 ], where the maximum working youth population of Nepal was reported to lie between 25–45 years of age group. This research finding has a minimum percentage of producers above 60, which is against the finding of some researchers from Bahrain [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The age distribution of producers revealed that the maximum number of people involved in Chhurpi production was in between 20–30 and 30–40 years of age. This result concurs with the findings of Paudel [ 37 ] and Nepali [ 38 ], where the maximum working youth population of Nepal was reported to lie between 25–45 years of age group. This research finding has a minimum percentage of producers above 60, which is against the finding of some researchers from Bahrain [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, family structure of producers found in our study strongly coincides with the findings of Nepali, i.e. the majority of the producers belong to nuclear families [ 38 ] this might be due to the movement of the people from hilly areas to Terai in search of a better opportunity, to find a job, or education etc.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations